Intelligent music production - De Man, Brecht; Stables, Ryan; Reiss, Joshua D. (Audio Engineering Society Presents.., 2020)
"Intelligent Music Production presents the state of the art in approaches, methodologies and systems from the emerging field of automation in music mixing and mastering. This book collects the relevant works in the domain of innovation in music production, and orders them in a way that outlines the way forward: first, covering our knowledge of the music production processes; then by reviewing the methodologies in classification, data collection, and perceptual evaluation; and finally by presenting recent advances on introducing intelligence in audio effects, sound engineering processes, and music production interfaces. Intelligent Music Production is a comprehensive guide, providing an introductory read for beginners, as well as a crucial reference point for experienced researchers, producers, engineers and developers"--